Enhancing Arabic Vocabulary Learning through ActiveInspire Interactive Media: A Quasi-Experimental Study in Islamic Secondary Education: تحسين تعلم المفردات العربية من خلال الوسائط التفاعلية أكتيف إنسباير: دراسة شبه تجريبية في التعليم الثانوي الإسلامي - Kamaluddin Kamaluddin; Septika Rudiamon; Achmad Yani; Olivia Levan's; Nurlaila Nurlaila; Rizka Widayanti (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
Vocabulary mastery constitutes a fundamental component of Arabic language learning, yet conventional instructional approaches often fail to foster active student engagement and effective vocabulary retention. This study investigated the effectiveness of ActiveInspire as an interactive digital learning medium for improving Arabic vocabulary mastery among junior secondary students. A quantitative approach with a quasi-experimental, non-equivalent control group design was employed. The participants comprised 20 ninth-grade students at Madrasah Tsanawiyah Negeri 17 Tanah Datar, assigned to an experimental group and a control group. Data were collected through classroom observations, interviews, documentation, and vocabulary achievement tests, and analyzed using normality, homogeneity, and independent t-tests. The findings revealed a statistically significant difference between the two groups, with the calculated t-value (3.27) exceeding the critical t-value (2.10), confirming the positive effect of ActiveInspire on students' vocabulary mastery. Students exposed to ActiveInspire demonstrated greater vocabulary acquisition, retention, and contextual use than those receiving conventional instruction. These findings provide empirical evidence that interactive digital media can enhance vocabulary learning outcomes while promoting classroom engagement, suggesting that ActiveInspire represents a promising pedagogical tool for technology-enhanced Arabic language instruction.